265 Incidence, determinants and prognostic relevance of HS-troponin and natriuretic peptides elevation at admission in hospitalized COVID-19 pneumonia patients. (17th December 2020) - Arcari, Luca; Luciano, Michelangelo; Cacciotti, Luca; Musumeci, Maria Beatrice; Spuntarelli, Valerio; Pistella, Eleonora; Martolini, Dario; Manzo, Daniele; Pucci, Mariateresa; Marone, Claudio; Melandri, Serena; Ansalone, Gerardo; et al.
Abstract: Aims: myocardial involvement in the course of Coronavirus disease 2019 (COVID-19) pneumonia has been reported, though not fully characterized yet. Aim of the present study is to undertake a joint evaluation of hs-Troponin and natriuretic peptides (NP) in patients hospitalized for COVID-19 pneumonia. Methods and results: in this multicenter observational study, we analyzed data from n = 111 COVID-19 patients admitted to dedicated "COVID-19" medical units. Hs-Troponin was assessed in n = 103 patients and NP in n = 82 patients on admission; subgroups were identified according to values beyond reference range. increased hs-Troponin and NP were found in 38% and 56% of the cases respectively. As compared to those with normal cardiac biomarkers, these patients were older, had higher prevalence of cardiovascular diseases (CVD) and more severe COVID-19 pneumonia by higher CRP and D-dimer and lower PaO2/FIO2. Two-dimensional echocardiography performed in a subset of patients (n = 24) showed significantly reduced left ventricular ejection fraction in patients with elevated NP only (p = 0.02), whereas right ventricular systolic function (tricuspid annular plane systolic excursion) was significantly reduced both in patients with high hs-Troponin and NP (p = 0.022 and p = 0.03 respectively). On multivariable analysis, independent associations were found of hs-Troponin with age, PaO2/FIO2 and D-dimer (B = 0.419, p = 0.001; B=-0.212, p = 0.013 and B = 0.179, p = 0.037 respectively), and of NP with age and previous CVD (B = 0.480, p < 0.001 and B = 0.253, p = 0.001 respectively). In patients with in-hospital mortality (n = 23, 21%) hs-Troponin and NP were both higher (p = 0.001 and p = 0.002 respectively), while increasing hs-troponin and NP were associated with worse in-hospital prognosis [OR 4.88 (95% CI 1.9-12.2), p = 0.001 (adjusted OR 3.1 (95% CI 1.2-8.5), p = 0.025) and OR 4.67 (95% CI 2-10.8), p < 0.001 (adjusted OR 2.89 (95% CI 1.1-7.9), p = 0.04) respectively]. Receiver operator characteristic curves showed good ability of hs-Troponin and NP in predicting in-hospital mortality (AUC = 0.869 p < 0.001 and AUC = 0.810, p < 0.001 respectively). Conclusion: myocardial involvement at admission is common in COVID-19 pneumonia and associated to worse prognosis, suggesting a role for cardiac biomarkers assessment in COVID-19 risk stratification. Independent associations of hs-Troponin with markers of disease severity and of NP with underlying CVD might point towards existing different mechanisms leading to their elevation in this setting.